Appointment-Based Queue Management System Using Geolocation Information - Tee, Kah Hui (Universiti Sains Malaysia, 2017)
Queues are often seen in hospitals across Malaysia. Majority of outpatient departments (OPD) receive patients by unscheduled walk-in which results in an uncontrollable and unpredictable arrival rate. When the arrival rate exceeds the service capacity of OPD, a queue is formed. Patients are required to queue for more than two hours at OPD in Malaysia government hospital. Hence, reduction of waiting time is one of the major issues that need to be tackled. Previous works have never consider reducing the waiting time by controlling the arrival rate of OPD patient. This work aims to develop an appointment-based queue management system using geolocation information (GeoQueue) to tackle long queues. A current OPD queue model was simulated with discrete-event simulation (DES) method. Average waiting time of a queue was obtained as the performance index. GeoQueue was developed to provide the patients a time slot to arrive at OPD based on their geolocation information. Result from that, the arrival rate of patient is controllable and predictable. A uniform arrival rate of 16 patients per hour was achieved with GeoQueue. Simulation model reveals that the GeoQueue realizes a shorter waiting time for patients. Average waiting time of patients had been reduced by 62%.